Reportage photography in the news press as a propaganda and promotion tool of scouting in southern Brazil and Spain in the early decades of the 20th century - Martiarena de Oliveira, Maria Augusta; Sureda García, Bernat (Historia y Memoria de la Educación, 2018)
This article looks at the propaganda-driven coverage of boy scouts in the illustrated press in southern Brazil and Spain in the early decades of the 20th century. We have used published photographs from magazines of the period for our study. The article shows how the institutions of power in Brazil and Spain used photographs to reinterpret the scout method created by the British soldier Robert Baden-Powell to provide young boys with patriotic training through discipline and order, instilling a positive disposition towards militarism. The First World War, the post-war period and the social and economic crisis of the time created the necessary backdrop for a patriotic zeal that found a way to indoctrinate and promote military training for young people through the scout method. The published images of boyscout troops, set up in both countries shortly after the creation of the movement in England, generally show them participating in activities that involve subordination to power and rigorous discipline. In contrast, there are few photographs that show exclusively the more fun, playful aspects of the method, or its use of active education